Smoking - Gano, Lila, 1949- (San Diego, CA : Lucent Books, 1989)
Discusses major issues relating to smoking, including its relation to American culture, economy, and disease.
Includes index.
Bibliography: p. 87.
Keywords: Tobacco use -- United States -- Juvenile literature; Smoking -- United States -- Juvenile literature; Smoking